2015
DOI: 10.1111/nph.13745
|View full text |Cite
|
Sign up to set email alerts
|

Tomato MBD5, a methyl CpG binding domain protein, physically interacting with UV‐damaged DNA binding protein‐1, functions in multiple processes

Abstract: SummaryIn tomato (Solanum lycopersicum), high pigment mutations (hp-1 and hp-2) were mapped to genes encoding UV-damaged DNA binding protein 1 (DDB1) and de-etiolated-1 (DET1), respectively.Here we characterized a tomato methyl-CpG-binding domain protein SlMBD5 identified by yeast two-hybrid screening using SlDDB1 as a bait.Yeast two-hybrid assay demonstrated that the physical interaction of SlMBD5 with SlDDB1 is mediated by the C-termini of SlMBD5 and the b-propeller-C (BPC) of SlDDB1. Coimmunoprecipitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 79 publications
(113 reference statements)
2
31
0
Order By: Relevance
“…The blocked membranes were incubated with anti‐HA, anti‐FLAG or anti‐H3K27me3 for another 2 h, respectively. These membranes were then washed three times for 10 min with 1× TBST buffer and incubated for 1 h with appropriate horseradish peroxidase (HRP)‐conjugated secondary antibody in blocking buffer (Li et al , 2015). Enhanced chemiluminescence detection was performed as recommended by the manufacturer (Millipore Corp.).…”
Section: Methodsmentioning
confidence: 99%
“…The blocked membranes were incubated with anti‐HA, anti‐FLAG or anti‐H3K27me3 for another 2 h, respectively. These membranes were then washed three times for 10 min with 1× TBST buffer and incubated for 1 h with appropriate horseradish peroxidase (HRP)‐conjugated secondary antibody in blocking buffer (Li et al , 2015). Enhanced chemiluminescence detection was performed as recommended by the manufacturer (Millipore Corp.).…”
Section: Methodsmentioning
confidence: 99%
“…MBD6 not only participates in RNA-mediated gene silencing in combination with 40S ribosomal protein AtRPS2C, AtAGO4, and nuclear transport factor AtNTF2, but it also binds to the histone deacetylase AtHDA6 in the RdDM pathway [32]. Studies in tomato (Solanum lycopersicum L.) have shown that MBD5 interacts with the CUL4-DDB1-DET1 complex, affecting its assembly on methylated DNA and thereby impairing the transcriptional activation of downstream genes [33].The different molecular functions of MBD proteins indicate that they play different roles in plant growth and development. In Arabidopsis, MBD genes are expressed in a tissue-specific manner, except for AtMBD11, which is highly expressed in all tissues [30].…”
mentioning
confidence: 99%
“…Arabidopsis MBD7-1 mutants have low SUCROSE-PROTON SYMPORTER2 (SUC2) expression and develop long roots when cultivated on a sucrose-containing medium [31]. Overexpressing SlMBD5 in tomato led to dark fruit color and dwarf plants [33].To date, few studies have focused on MBD proteins in plants, especially woody plants. In the current study, we cloned the coding region of the MBD gene SvMBD5 from the woody plant Salix viminalis L. and analyzed its expression pattern and biological function.…”
mentioning
confidence: 99%
See 2 more Smart Citations